A bibliometric analysis of process system failure and reliability literature. (December 2019) - Amin, Md. Tanjin; Khan, Faisal; Zuo, Ming J.
Abstract: This paper presents a bibliometric analysis of process system failure and reliability studies. This analysis attempts to answer following questions, related to the evolution of failure and reliability engineering in process system: (i) What are the key areas? (ii) What are the major tools and their evolution and frequency of use? (iii) How much global popularity does this field possess? (iv) Which countries are active in these areas of research? (v) Who are the top contributing authors? (vi) What is the principal source of documents in this field? (vii) What are the prevalent factors behind the citations? and (viii) What is the contribution of the industries? This field is found to have a sharp increase in the number of documents in the last twelve years (2006–2018). It is observed that process reliability is a global topic, with an active participation from the USA, China, India, and Norway. Methodology, reliability model, and maintenance-related journal articles cover the colossal portion of the documents, and conferences are the most popular mean of industrial documents. IEEE Transactions on Reliability, Reliability Engineering & System Safety, Microelectronics Reliability, and Engineering Failure Analysis are the chief sources of documents. Despite a vital contribution from industry, collaborative works between industry and academia are observed to be rare. Highlights: A bibliometric analysis of process system failure and reliability engineering from inception to January 2019. Study answers eight questions related to the evolution of failure and reliability engineering in process systems. Methodology, reliability model, and maintenance-related journal articles cover the colossal portion of the documents. Conferences are the chief sources of industrial documents. Despite a vital contribution from industry, collaborative works between industry and academia are observed to be rare.